Large Plaque-type Blue Nevus with GNAQ Q209P Mutation, Involving Mammary Gland Tissue: Under-Recognized Mammary Condition as an Origin of Primary Mammary Melanocytic Tumors. (December 2021) - Satake, Kosuke; Sudo, Tamotsu; Sugino, Takashi; Yoshikawa, Shusuke; Kiyohara, Yoshio; Hayashi, Tomomi; Nakashima, Kazuaki; Goto, Keisuke
Abstract : Abstract: Plaque-type blue nevus is a rare variant of blue nevi that was first described in 1954. This article presents clinical, macroscopic, histopathological, and genetic findings for a case of large plaque-type blue nevus expanding into the mammary gland tissue as well as the skin of the right breast. A 63-year-old woman presented with a congenital, large, blue-colored macule limited to the hypochondriac area of the right breast. A nodule 8 mm in diameter was also present in the mammary gland tissue. Magnetic resonance imaging was unable to detect diffuse melanin deposition in the mammary gland tissue, but pigmentation in the whole mammary parenchyma was observed in the cut surfaces of the mastectomy specimen. Histopathology revealed a sparse distribution of dendritic melanocytes in whole sections of the mammary fibrous tissue and partial sections of the dermis. The histopathological criteria for atypical cellular blue nevus were fulfilled for the mammary tumor. Nodal blue nevus was diagnosed in the sentinel lymph node. Sanger sequencing confirmed the GNAQ Q209P mutation, which was also identified in all 4 literature cases of plaque-type blue nevus, but rarely in conventional blue nevi and uveal melanoma. It should be noted that plaque-type blue nevus can expand into the mammary gland tissue, even if the pigmented lesion does not exist on the overlying breast skin. The mammary condition can be the origin of primary mammary melanocytic tumors. Mosaicism of the GNAQ Q209P mutation can be a characteristic genetic alteration to extensive blue nevi, including plaque-type blue nevus.